MK4: On water governance - Sajor, Edsel (2006)
This project focuses on the governance structures and mechanisms needed to enable, support and maintain successful WSI optimization strategies.The latter research relates not only to individual reservoirs, but also to cascades, including transboundary cascades. It draws on other Mekong BDC projects as well as institutional analysis of current water governance for different uses. Water management and governance for multiple uses need to move beyond traditional and sectoral approaches.This project will not aim at developing a single blue-print for governance, but rather will identify and evaluate a range of options that can support stakeholders’ choices and decisions – link with Project 5 for stakeholder participation in resource research development and resource management.